If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + -5 + -1g + -5g = 0 Reorder the terms: -5 + 5g + -1g + -5g = 0 Combine like terms: 5g + -1g = 4g -5 + 4g + -5g = 0 Combine like terms: 4g + -5g = -1g -5 + -1g = 0 Solving -5 + -1g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1g = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1g = 0 + 5 -1g = 0 + 5 Combine like terms: 0 + 5 = 5 -1g = 5 Divide each side by '-1'. g = -5 Simplifying g = -5
| 3(x+2)+9=3x+8 | | 4+6=-9+7 | | m-7m-3m-5= | | 2+7+x=16 | | -4x^2-9x-4=0 | | 4x+3.2=8.8 | | 5(x-3)+2=3x+2(-5+x) | | 2+(x+4)+8x=8 | | f(x)=-4x^2-9x-4 | | -5-(-30)=x/9 | | -5(4y-6)-y=-2(y-3) | | 4t-8=10 | | -4(8x+5)-6=-32x-26 | | 11.7+x-8.4=3.7 | | 4(5x-10)=20(x-10) | | 2(tx-8)-4x=10 | | 6(5k-3)=8k+4 | | (x+4)(x-1)=36 | | 5n^2+45n=0 | | -3.9=12.1-4y | | vf=vi-gt | | 54x-40=7(7x-6)+5x+2 | | Xy+3x=6 | | 26x+15=5(5x+4) | | 22-v/3=-7 | | -10+x-9=11-15+5 | | 2x-(15-7x)=120 | | 5-(-2y+2)= | | (3x-10)(x+40)=180 | | 5(2x-1)-2(3x+4)=3 | | 4(x-1)-1=2x+2(-1+x) | | 2x+5=5+3x-1 |